Time for architecture : on modernity, memory and time in architecture and urban design - Adam, Robert (Cambridge Scholars Publishing, 2020)
"Using time as a unifying theme, this book critically analyses many of the key concepts in modern architecture and urban design, such as modernity, innovation, timelessness and sustainability. Drawing on the statements of contemporary architects and with reference to a wide range of sources from history, philosophy, sociology and anthropology, as well as studies in diverse subjects such as science fiction, colonialism and archaeology, the text provides a new perspective on much of the thinking behind contemporary design. In addition, it develops original and practical theories on the meanings of modernity, the variable ageing of the environment, the central role of longevity in sustainability, the significance of authenticity in conservation, and the relationship between collective memory and tradition"--Provided by publisher.